A Rare Case of an Uterine Intravenous Leiomyomatosis - Karataş Şahin, Ediz; Yüksel, Dilek; Ünsal, Mehmet; Güler Mesci, Çiğdem; Müftüoğlu, Kamil Hakan; Kınay, Tuğba; Korkmaz, Vakkas (Cerrahpaşa Medical Journal, 2021)
Intravenous leiomyomatosis is a rare benign neoplasm originating from smooth muscle cells. Although histopathologically benign, its behavior may be aggressive and fatal outcomes can occur. However, it is very difficult to diagnose this entity, and intravenous leiomyomatosis is usually only suspected intraoperatively or after pathological analysis. In this article, we presented an interesting case of intravenous leiomyomatosis who was diagnosed intraoperatively and complicated with massive bleeding. Subsequent histopathological and immunohistochemical examination confirmed the diagnosis as intravenous leiomyomatosis. Nadir Bir Uterin İntravenöz Leiomyomatozis Olgusu İntravenöz leiomyomatozis düz kas hücrelerinden köken alan nadir görülen benign bir neoplazmdır. Histopatolojik olarak iyi huylu olmasına rağmen davranışı agresif olabilir ve ölümcül sonuçlar ortaya çıkabilir. Ancak teşhisi çok zordur ve intravenöz leiomyomatozis genellikle sadece intraoperatif olarak veya patolojik analizden sonra şüphelenilir. Bu makalede intraoperatif tanı konulan ve masif kanama ile komplike olan ilginç bir intravenöz leiomyomatozis olgusunu sunduk. Takiben histopatolojik ve immünohistokimyasal inceleme ile tanı intravenöz leiomyomatozis olarak doğrulandı. Cite this article as: Karataş Şahin E, Yüksel D, Ünsal M, et al. A rare case of an uterıne intravenous leiomyomatosis. Cerrahpaşa Med J. 2022;46(1):83-85.